How do managers sense Business Model Innovation opportunities and threats? - Verronen, Tuomas (My University, 2023)
Fight against the climate change has a great effect on energy sector, which leans strongly on fossil fuels. New technologies, e.g., wind and solar power, bring new challenges for electricity production due to their intermittency. Technological developments enable consumers to produce electricity themselves. Due to these reasons electricity companies must question and innovate their business models to stay competitive and to reason their existence. In this study, we will research business model innovation from cognitive approach, and we aim to find answers, how managers find possibilities to innovate business models or how they sense threats to business models, so that their negative effects can be mitigated. The literature of cognition and business model innovation are the theoretical basis for the study. A link between the two will be built using dynamic capabilities. Two key elements of the theoretical model are attention and perception, which will be explained in detail. The research method will be multiple-case study. Five electricity companies participated in the study. The data collection was done using semi-structured interviews. Both within-case analysis and cross-case analysis were done. Lastly, the results were compared with the literature for better credibility and reliability. With the empirical data it was concluded, that managers’ attention and perception are complex processes and they comprise of multiple factors, dimensions, and elements. The attention focus is determined by internal, customer and stakeholder, and external factors. These factors can be divided into signals, that guide the focus on specific things, and into results, which are searched in the environment. Managers can be categorized based on the approaches, whether they distinguish the observations into opportunities and threats, or if they see elements of opportunities and threats in each observation. Managers can be categorized into three groups by the reactions to observations: optimists, realists, and defenders. Optimists aim to approach each observation as opportunity, for the realists only the impact of the observation matters, and the defenders act more on threats. This thesis builds the overall knowledge of the elements and how the sensing dynamic capability manifests itself in the form of attention and perception. The implications include a novel theoretical framework to research opportunity and threat recognition as the sensing dynamic capability of business model innovation. It allows future research to understand better how attention and perception occur to sense business model innovation-related opportunities and threats. The thesis enables managers to reflect on their behavior and approaches, and to develop their cognitive capabilities and thus increase competitive advantage.

Taistelulla ilmastonmuutosta vastaan on suuri vaikutus energia-alalle, joka on nojannut vahvasti fossiilisiin polttoaineisiin. Uudet teknologiat, kuten tuuli- ja aurinkoenergia, tuovat omat haasteensa sähköntuotannolle niiden epäsäännöllisyyden vuoksi, mutta teknologioiden kehitys myös mahdollistaa kuluttajille oman tuotannon ihan uudessa laajuudessa. Näistä syistä sähkönmyyjien tulee kyseenalaistaa ja innovoida heidän liiketoimintamalleja pysyäkseen kannattavina ja ylipäätään perustellakseen olemassaolonsa. Tässä työssä tutkitaan liiketoimintamallien innovointia kognition näkökulmasta, ja pyritään löytämään vastauksia, miten johtajat löytävät mahdollisuudet innovoida tai miten he havaitsevat uhkat liiketoimintamalleille, jotta niiden negatiiviset vaikutukset voidaan minimoida. Työn teoreettisena pohjana toimii kirjallisuus liiketoimintamalli-innovaatiosta ja kognitiosta, joiden välille luodaan silta dynaamisten kyvykkyyksien avulla. Teoreettisen mallin kaksi avainelementtiä ovat huomiointi ja tulkinta, jotka käydään tarkemmin lävitse. Tutkimusmenetelmänä käytetään monitapaustutkimusta, johon osallistui viisi kuluttajasähkönmyyntialan yritystä. Aineiston keräämiseen käytettiin osittaisstrukturoituja haastatteluja. Aineisto analysoitiin sekä tapauskohtaisesti, että ristikkäisanalyysillä. Lisäksi tuloksia verrattiin teoriaan tutkimuksen luotettavuuden varmistamiseksi. Tutkimuksen tuloksena todettiin, että johtajien huomiointi ja tulkinta ovat monimutkaisia prosesseja ja koostuvat useasta tekijästä, ulottuvuudesta ja elementistä. Huomioinnin kohteen määrittämiseen vaikuttaa sekä sisäisiä, asiakas ja sidosryhmätekijöitä, kuin ulkoisia tekijöitäkin, ja nämä voidaan jaotella sekä signaaleihin, jotka kääntävät huomion tiettyyn asiaan, mutta myös tuloksiin, joita pyritään löytämään. Johtajat voidaan ryhmitellä sen tulokulman mukaan, jaottelevatko he havainnot mahdollisuuksiin vai uhkiin, vai näkevätkö he jokaisessa havainnossa elementtejä molemmista. Havaintoihin reagoimisen suhteen johtajat voidaan jakaa kolmeen ryhmään: optimisteihin, realisteihin ja puolustajiin. Optimistit pyrkivät suhtautumaan havaintoihin mahdollisuuksina, realistille vain havainnon vaikutuksella on väliä, ja puolustajat reagoivat enemmän uhkiin. Tässä tutkimuksessa lisättiin näyttöä kognition ja liiketoimintamalli-innovoinnin väliselle yhteydelle. Työssä luotiin teoreettinen malli, jota voidaan hyödyntää tulevaisuuden tutkimuksessa. Johtajille tulokset antavat mahdollisuuksia reflektoida omia tulokulmia kognitioon ja siten kehittää omia kognitiivisia kyvykkyyksiä ja lisätä yrityksen kilpailuetua.
Keywords: business models; innovations; cognition; attention; perception (activity); fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development